How to Quadruple the Reach and Value of Your NREN - (:unkn) unknown (My University, 2015)
Australia and Africa have much in common – vast distances, sparse population, heat, rain and of course the Square Kilometre Array (SKA). AARNet Pty Ltd (AARNet) is the Australian Research and Education Network in Australia (NREN). The building of long term and sustainable physical infrastructure has been one of the key strategies in building AARNet into what it is today; one of the worlds most advanced NRENs. Some 12 years ago, and almost by accident, AARNet became involved in major civil works projects simply because it could not procure dark fibre or services at a reasonable cost. Australia is either world’s largest island or the world’s smallest continent and this presentation will detail the journey in building more than 30,000 pair kilometres of dark fibre infrastructure, connecting every University, many schools, hospitals and research centres, across some 7 million square kms of the “wide brown land”. Today the network stretches from the northern tip of Australia, transiting some of the most inhospitable terrain to Western Australia, now the home of the Australian SKA. It has become vital underpinning infrastructure for sensor networks in the Great Barrier Reef and building it has been a fascinating challenge. Infrastructure begets infrastructure. Having built the initial fibre tails to its major customers, AARNet had currency. It had right and title to its own assets and was able to swap fibre pairs with councils, energy companies and other telecommunications carriers doubling that asset. It swapped many times over doubling the fibre footprint. It built a reputation for being a small and dynamic civil works group and soon was asked to partner with other carriers looking to build into remote and regional areas. AARNet simply built one side of a fibre ring and the partner built the other. AARNet proved to be a non-competitive partner simply looking for a lifetime interest in dark fibre. Today AARNet has more than quadrupled its fibre footprint courtesy of simply having taken the initial step to build fibre tails into the backbone network. Above the network products and services are now very important to AARNet but we recognise that we will do nothing without the ‘network’. This presentation will explore what worked and what didn’t; a virtual cookbook for building an NREN looking for a long term and economic competitive edge. Examples will be given for how to create a “dial before you dig system”, how to contract with civil works partners, how to partner with other infrastructure owners such as energy companies where there are specific requirements relating to regulated income, and how to deal with incumbent and dominant telecommunications carriers. Finally and most importantly the presentation will outline how message to government and relevant national and international funding bodies the return on investment in an NREN with long term sustainable research infrastructure.
Keywords: NREN; Research